Holding on to the Goal or Letting It Go and Moving On? A Tripartite Model of Goal Striving - Ntoumanis, Nikos; Sedikides, C. (2018)
© The Author(s) 2018. Recent findings challenge the widely held motto of “never give up” in goal striving. There are situations in which it is of strategic interest to abandon an important goal and allocate resources to an alternative goal. The ability to realize whether a goal is attainable or not (and therefore the ability to make the “right choice” between goal persistence and goal disengagement or reengagement) is influenced by at least two key motivational factors: motivation for goal striving and a self-regulatory technique called mental contrasting with implementation intentions. The interplay between these two factors is as yet unexplored but holds promise for several conceptual and practical advancements in understanding the pursuit of challenging life goals. To this end, we propose a tripartite model of goal striving that integrates goal motivation and goal regulation.